Live Shopping dan Minat Beli Konsumen dalam E-Commerce: Tinjauan Literatur Sistematis - Kinanti Putri Kusumah Lestari; Kurnia Khafidhatur Rafiah; Muhammad Rifqi Arviansyah (Universitas Airlangga, 2025)
The advancement of technological development in the digital business world proliferates from time to time. The use of Internet networks for daily needs is increasing rapidly, especially for buying and selling transactions. Therefore, live shopping technology has emerged as a new shopping trend nowadays. This study used qualitative methodology by doing a literature review of 20 relevant international journals published between 2019 and 2023. The database used for this systematic literature review is Scopus. This study aims to define live-streaming shopping and purchase intention and find its influence on purchase intention from prior studies. This study aims to systematically review factors influencing consumers’ purchase intention in live-streaming shopping. The findings indicate that live-streaming shopping significantly impacts viewers’ purchase intention through various factors, including interactivity between viewers and streamers, engagement, trust, price, promotion strategies, influencers, and Key Opinion Leaders (KOL). Furthermore, the study reveals that most prior research in this area applied a quantitative approach using PLS-SEM or CB-SEM. However, existing literature suggests that future research should incorporate mixed-methodology to gain a more comprehensive understanding. This study contributes by highlighting the correlation between live-streaming shopping and purchase intention, as well as the dominant research methodologies used in previous studies. The findings provide valuable insights for businesses and researchers in understanding consumer behavior in live-streaming shopping environments.